Determinants and impacts of digital library usage: a survey among selected Iranian universities / Ismail Samadi - Samadi, Ismail (Institute of Graduate Studies, UiTM, 2017)
In the age of information, digital library (DL) adoption among Iranian universities and academic higher learning institutions has been very common. It is no longer considered as a lavish technological investment, but rather treated as technological need and necessity crucial to the survival of the university. Various studies have revealed that universities and academic higher learning institutions have benefitted from the installation of the digital libraries. In an academic environment, DL usage is purely volitional or optional. Innovative users would effectively use the DL for some specific reasons and objectives, while others may simply ignore it. This situation simply suggests that there are some determining factors that shape the usage behavior of the users. Given that digital libraries (DL) have been implemented in most Iranian universities and academic higher learning institutions, knowledge regarding users’ usage behavior is still very limited. Not much is really known about the extent users; especially students exploit the DL for the purpose of enhancing their performance and productivity. Similarly, little is really known about the factors that shape Iranian students’ DL usage behavior from users’ lenses. To this effect, this study is aimed to investigate the usage behavior of users in a DL environment in selected Iranian universities. In addition, it is also aimed at investigating the determinants of DL usage behavior. Finally, this study also intends to investigate the impact of DL usage behavior among users. The conduct of this study was using a quantitative approach...